2011
DOI: 10.1111/j.1524-4741.2011.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: Management and Follow-up Recommendations

Abstract: National Comprehensive Cancer Network (NCCN) guidelines for female breast cancer treatment and surveillance are well established, but similar guidelines on male breast cancers are less recognized. As an NCCN institution, our objective was to examine practice patterns and follow-up for male breast cancer compared to established guidelines for female patients. After Institutional Review Board approval, a prospective breast database from 1990 to 2009 was queried for male patients. Medical records were examined fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 40 publications
5
32
0
3
Order By: Relevance
“…A recent example is reported from the Moffitt Cancer Center, looking at their 20-year experience of over 19,000 patients treated for breast cancer. 12 Only 73 (0.4 %) were men, and of these, only 62 had sufficient data recorded for inclusion in the study. The largest population-based data repository in the United States is the surveillance, epidemiology, and end results (SEER) program, a registry program of the National Cancer Institute, but it collects data from only a limited sample of registries in just 12 states, mainly on the basis of ''their ability to operate and maintain a high quality population-based cancer reporting system and for their epidemiologically significant population subgroups.''…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is reported from the Moffitt Cancer Center, looking at their 20-year experience of over 19,000 patients treated for breast cancer. 12 Only 73 (0.4 %) were men, and of these, only 62 had sufficient data recorded for inclusion in the study. The largest population-based data repository in the United States is the surveillance, epidemiology, and end results (SEER) program, a registry program of the National Cancer Institute, but it collects data from only a limited sample of registries in just 12 states, mainly on the basis of ''their ability to operate and maintain a high quality population-based cancer reporting system and for their epidemiologically significant population subgroups.''…”
Section: Discussionmentioning
confidence: 99%
“…Lartigau et al reported a significant difference in 10-year disease-specific survival between those with T4 and those with T1 tumors (32% versus 87%, p=0.001) (11); Cutuli et al reported 10-year disease-specific survival rates for those with T0-T1, T2 and T3-T4 of 81%, 80% and 69%,respectively (20). Lymph node involvement was a strong prognostic factor in most MBC studies (15,31,34,36,37). The 10-year survival was 28% when lymph nodes were not involved versus 58% when involved (12).…”
Section: Resultsmentioning
confidence: 99%
“…In node positive patients, the five and ten year survival rate decrease to 73% and 50% respectively. Due to advanced stage of neoplasm at the time of presentation, Modified Radical Mastectomy is the most often operation in male breast cancer [15] . Role of Breast-conserving therapy in male breast cancer is unclear [16] .…”
Section: Discussionmentioning
confidence: 99%